A review on the mineralization of organic pollutant by using perovskite catalyst / Nurul Elia Aqila Abu Rahim, Rasyidah Alrozi and Dr. Norhaslinda Nasuha - Abu Rahim, Nurul Elia Aqila; Alrozi, Rasyidah; Nasuha, Norhaslinda (2020)
This study aspires to have an improvement of Advance Oxidation Process (AOPs) to degrade organic pollutants. Currently, AOPs need chemical additives and additional energy that is not economically. Perovskite catalyst have been introduced to degrade existing organic pollutants preferred to economic saving and feasible operation. This study therefore aims to review the mineralization of organic pollutants using perovskite catalyst by Total Organic Compound (TOC) analysis and to review the intermediate compound presence during catalysis by High Performance Liquid Chromatograph (HPLC). Methodology of research review including identify the problem, literature review, data collection, data verification, data analysis and conclusion. Zinc Oxide (ZnO) perovskite catalyst used to degrade 4 types of dyes solution which are yellow 145 dye, black 5 dye, Red 4 dye, and Blue 21 for initial time, 30 minutes and 2 hours for mineralization process. Graphical presentation of the study shows that the longer the time taken for mineralization process, the higher the mineralization rate. The present study demonstrates that the ZnO type of perovskite catalyst is an efficient and feasible method to treat textile wastewater. TOC removal in degradation of azo II dye solution using calcium strontium copper (CSC) based catalyst under dark condition without any ozone or peroxide has been studied. The content of Ca and Sr in the A-site of the perovskite structure was varied whilst the B-site was Cu rich. CSC compounds with higher Ca content in the A-site were slightly more effective at degrading OII. In order to understand further the by-product formation during the catalytic activity, the HPLC analysis carried out for OII dye solutions degradation from 0 to 240 minutes. The highest intermediate compound that exist in the reaction are at mass-to-charge ratio of 327.04 m/z which is C10H11N2O4S. As for the contact time increase, more reactant adsorbed on the catalyst surface.